MACROECONOMIC VARIABLES AND STOCK PRICE VOLATILITY IN NIGERIA - OSAZEE GODWIN OMOROKUNWA; NOSAKHARE IKPONMWOSA (Annals of the University of Petrosani: Economics)
The purpose of this paper is to examine the relationship between stock price volatility and few macroeconomic variables such as inflation, exchange rate, GDP and interest rate. Annual time series data ranging from 1980 to 2011 was used for this study. The generalized autoregressive conditional heteroskedasticity (GARCH) model was used in the empirical analysis. The findings of the study showed that stock prices in Nigeria are volatile. And that past information in the market have effect on stock price volatility in Nigeria. In addition, the study showed that interest rate and exchange have a weak effect on stock price volatility while inflation is the main determinant of stock price volatility in Nigeria. The authors recommend that inflation should be targeted as the main monetary policy aimed at directing the stock market.